2006
DOI: 10.1007/s00106-006-1506-4
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation der Hochtoninnenohrschwerhörigkeit

Abstract: The middle ear implant Vibrant Soundbridge has been shown to be perform extremely well especially in the high frequencies. It offers a new solution for rehabilitation of high frequency hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The VORP is set in an appropriately drilled out bone bed. The audiological indication is mild to moderate hearing loss with low losses of up to 1 kHz, whereas due to the better efficiency of the transducer in a higher frequency range, stronger losses can be compensated [158], [159]. The highest auditory threshold gain is between 1 and 2 kHz between 28–37 dB [160], [161], [162], [163] with good long-term stability [164].…”
Section: Active Middle Ear Implantsmentioning
confidence: 99%
“…The VORP is set in an appropriately drilled out bone bed. The audiological indication is mild to moderate hearing loss with low losses of up to 1 kHz, whereas due to the better efficiency of the transducer in a higher frequency range, stronger losses can be compensated [158], [159]. The highest auditory threshold gain is between 1 and 2 kHz between 28–37 dB [160], [161], [162], [163] with good long-term stability [164].…”
Section: Active Middle Ear Implantsmentioning
confidence: 99%
“…It is shown that the Vibrant Soundbridge provides high gain especially in the high frequencies leading to better speech comprehension in noise [24, 25]. …”
mentioning
confidence: 99%